ASSOCIATION OF OBESITY AND PSORIASIS: A TEN YEARS SYSTEMATIC REVIEW - Kusuma Wardani, Putri; Nurul Ilmi, Yhoaninda (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Psoriasis as a chronic inflammatory condition is often linked with metabolic disorders such as obesity, diabetes, dyslipidemia, and fatty liver disease. Research indicates a strong association between obesity and psoriasis, with obese individuals having a higher risk and severity of the condition. This study aims to systematically the association between psoriasis and obesity in literatures of the last 10 years. Methods: This systematic review complied with the PRISMA 2020 standards and focused on full-text English literature published between 2014 and 2024. Articles such as editorials and review papers from the same journal, as well as submissions lacking a DOI, were excluded from consideration. Literature was sourced from online platforms like PubMed and SagePub. Result: We found 698 articles on PubMed and 1157 articles on SagePub. Restricting our search to the past decade (2014-2024), PubMed presented 606 articles, whereas SagePub presented 633 articles. From these, we selected 5 papers meeting our criteria, with 2 from PubMed and 3 from SagePub. Conclusion: Psoriasis is a chronic inflammatory skin disease caused by a complex interplay between immune and host cells. Obesity and nutrition play pivotal roles in its onset and severity through adipocytokin levels. Inflammation in psoriasis increases free radical production, necessitating antioxidants to maintain redox balance, suggesting that diets rich in antioxidants may help alleviate symptoms.